A flow cytometric method for characterization of circulating cell‐derived microparticles in plasma. Issue 1 (4th February 2014) - Nielsen, Morten Hjuler; Beck‐Nielsen, Henning; Andersen, Morten Nørgaard; Handberg, Aase
Abstract : Background and aim: Previous studies on circulating microparticles (MPs) indicate that the majority of MPs are of a size below the detection limit of most standard flow cytometers. The objective of the present study was to establish a method to analyze MP subpopulations above the threshold of detection of a new generation BD FACSAria™ III digital flow cytometer. Methods: We analyzed MP subpopulations in plasma from 24 healthy individuals (9 males and 15 females). MPs were identified according to their size (<1.0‐µm), by Lactadherin‐FITC labelling, and by exposure of cell‐specific markers. The sensitivity of the flow cytometer was tested against that of a previous‐generation instrument FC500. Reproducibility of the FACSAria and our set‐up was investigated, and the percentage of phosphatidylserine (PS) exposing MPs binding Lactadherin was determined. Results: By using a flow cytometric approach we identified and quantitated MPs derived from platelets, monocytes, erythrocytes and endothelial cells. In addition, levels of tissue factor‐positive MPs were determined. The FACSAria demonstrated improved sensitivity and increased MP detection range compared to the FC500 instrument. The reproducibility of PS+PMP and PS+MP measurements was 11.7 and 23.2%, respectively. When expressed as a percentage of total MPs, the PS‐positive MP population represented 15.1±5.5%, and PS‐positive MPs were significantly increased in men. Conclusion: We have established a method to measure MPs above the detection limit of a new generation flow cytometer and derived from a number of cell‐types in a healthy population of men and women.